An examination of past trends in school reports to child welfare: considerations for reported child maltreatment - Fallon, Barbara (Child maltreatment, 2022)
This study examines whether increased interaction and observation of young children by school professionals leads to an increase in school-based reports to child welfare authorities and in the identification of child maltreatment victims. Comparing provincial-level data collected before and after full-day kindergarten implementation in Ontario, a doubling in rates of school-referred investigations involving 4- and 5-year-old children was found. There was no significant difference in the rates of maltreatment substantiation, service referrals made or transfers to ongoing services, but the rate of child functioning concerns noted in these investigations tripled. The findings suggest there are differences in how the school and child welfare systems define and respond to suspected child maltreatment. Implications for practice, policy and research are explored.